Echocardiographic Assessment of Left Ventricular Function in Overweight and Obese Subjects - Jaber, Reem J.; Hassan, Affan E.; Taqa, Layth R. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Obesity is a public health concern worldwide associated with significant health risks and comorbid conditions. Obesity might be a strong factor that can induce left ventricular systolic dysfunction and eventually cause heart failure independent to coronary artery disease or other morbidities. In uncomplicated obese subjects, diastolic dysfunction is caused by hemodynamic and metabolic factors.Objectives: To assess the left ventricular (systolic and diastolic) function in a sample of overweight and obese subjects using different Echocardiographic tools and exploring the percentage and type of diastolic dysfunction in those people.Subjects and methods: one hundred seven (107) normal adult males subjects with a mean age of (39.3± 7.5) years were involved in this study. The study was performed during the period from September 2012 until July 2013, at the echo unit of Ibn Al-Bitar hospital for cardiac surgery.Results: Regarding E/A ratio there were statistically significant decrease in the E/A ratio of Group 1(normal body weight) when compared with that of Group3(obese). Deceleration time(DT), Isovolumetric relaxation time(IVRT) and E/Vp ratio showed a statistically significant increase when comparing Group1 with Group3. Regarding velocity of flow propagation(VP) there were statistically significant decrease when comparing Group1 with Group2 and Group 1 with Group3. Higher percent of subjects in group1 developed normal diastolic function(44%), while higher percent of subjects who found to have impaired relaxation were those in group3(68%), also higher percent of subjects with pseudonormal type were found in group3(57%) when compared to group1& 2.Conclusion: The relationship between BMI and diastolic function parameters is continuous and independent of cardiovascular risk factors that cluster with obesity, such as hypertension, diabetes, and LV hypertrophy. The overweight status is already associated with an impairment of LV diastolic function, close to that observed in obese persons.